Promoting Effective Writing through POW+TREE Strategy - Erniwati Erniwati; Sudarkam R Mertosono; Muhammad Arid; Afrillia Anggreni; Nirwijayanti Nirwijayanti (Universitas Cokroaminoto Palopo, 2022)
This study aims to determine if using POW+TREE Strategy effectively promotes writing skills of the sophomores of the English Education Study Program at Tadulako University on analytical exposition text. This is a pre-experimental study involving 20 participants selected purposively. The result showed that the POW+TREE Strategy successfully improves the participants’ writing skills on analytical exposition text. The participants found the strategy helpful in organizing and developing their logical arguments. Their writing performance and critical thinking skills are much improved resulting from the POW+TREE Strategy.